Study of fetomaternal arterial doppler parameters in early onset pre-eclampsia and its correlation with perinatal outcomes - Verma, Anju; Tomer, Shaili; Solanki, R. S.; Satija, Bhawna; Singh, Abha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Development of pre-eclampsia (PE) at less than 34 weeks of gestation is known as early onset PE (EOPE) and is commonly associated with more severe adverse maternal and fetal outcomes. The purpose of this study was to study Doppler parameters of uterine, umbilical and fetal middle cerebral arteries exclusively in women with EOPE and its correlation with perinatal outcomes. This study was a hospital-based observational prospective study. Methods: 60 patient of early onset PE with singleton live pregnancy were included in the study and followed up. The results of sonographic and Doppler examination were analysed and correlated with perinatal outcomes. Results: Adverse perinatal outcomes were seen in 66.66% cases of early onset PE. To predict adverse perinatal outcomes, umbilical artery (Umb A) RI, PI were found to be most sensitive, cerebroplacental ratio (CPR) was most specific indicator with highest positive predictive value (PPV). Absent end diastolic flow /reverse end diastolic flow (AEDF/REDF) were ominous signs. Conclusions: Early onset PE is recently considered a more severe disease with different etiopathogenesis. Doppler study is the primary imaging modality for fetomaternal surveillance for follow up and prediction of perinatal outcome, thus allowing planning of timely management in early onset PE patients, as these patients are at higher risk of adverse perinatal outcomes.